The Generics Act of 1988 policy formulation and implementation under pressure - Yadao-Guno, Carmelita (1991)
The Generics Act Law has stirred up controversial confrontations between those who advocate its existence and those who perceive it as a bane to the medical profession, if not to society as a whole. This article analyzes how and why the policy was even considered in the first place, the antecedent and existing circumstances which led to its formulation, the pressures brought to bear by factions directly or indirectly opposed to the measure, the manner by which all these were handled by the formulators of said policy and its gradual implementation in spite of the known obstacles surrounding it. The views of contending parties to this issue have also been dealt with in detail, including the final word on the matter as handed down by the final judicial arbiter of the land-the Supreme Court.
Keywords: Generics Act of 1988; Pharmaceutical industry; Pharmaceutical policy; Drug policy